Aktualisasi Sila Kedua dan Kelima dalam Edukasi Kesehatan Seksual dan Kekerasan Seksual di MTS Al-Misbah - Zeny Marliza; Rayhanun Sholehah; Hilma Saniyya Nabila; Lulu Siti Afifah; Albani Muhamad Zahra; Rafi Putra Ramadan; Aditya Rosadi; Mhd. Haqqil Ze; Agnia Jahrotul Hayya; Fajri Hidayatullah; Dian Herdiana; Nina Marlina (Yayasan Daarul Huda Kruengmane, 2025)
Pancasila, as the foundation of the state and the worldview of the Indonesian nation, provides moral guidance for all societal activities, including efforts to maintain health and prevent sexual violence. The values embodied in Pancasila must be realized concretely in daily life so that they do not remain merely ideal concepts, but truly shape the character of the nation. One important form of implementation is the cultivation of awareness regarding physical health, mental health, and self-protection from sexual violence from an early age. This is in line with the second principle, “Just and Civilized Humanity,” which emphasizes respect for human dignity, and the fifth principle, “Social Justice for All Indonesian People,” which mandates the fulfillment of safety and well-being for all citizens. In this Pancasila actualization activity, we provided education on the importance of maintaining reproductive health, understanding bodily boundaries, recognizing behaviors that may constitute sexual violence, and identifying the appropriate steps to report incidents either as victims or witnesses. The material was delivered through interactive methods, educational games, and light discussions to ensure it was easily understood by participants. This program aims to enhance awareness and courage within the community, particularly among adolescents, to protect themselves, maintain their health, and apply Pancasila values in addressing issues of sexual violence in their surrounding environment.